Eksistensi Upicc Sebagai Instrumen Soft Law Dalam Praktik Perdagangan Internasional - Valentina Gea, Gita Venolita (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
International trade practice is based on international treaties or agreements. Treaties in international law paradigm on its development now distinguished on the form of hard law or soft law. Soft law is identical with its characteristic as a legal instrument that has no juridical binding power. UPICC as a legal instrument on international trade sector tries to harmonize the international trade law but it has the nature of soft law. This paper aims to examine the purpose of UPICC existence on its effort of harmonizing the diversity of international trade law while its characteristic is defined as a soft law. Based on this research that was conducted by juridical-normative method, it is understood that the characteristic of UPICC as a soft law makes it as legal instrument that is able to adapt with the development of international trade law also to become the reference on reforming the international trade law. Key Words: UPICC, soft law, international trade.